Experimental Evidence on the Dependence of the Standard GPS Phase Scintillation Index on the Ionospheric Plasma Drift Around Noon Sector of the Polar Ionosphere. Issue 3 (25th March 2018) - Wang, Y.; Zhang, Q.‐H.; Jayachandran, P. T.; Moen, J.; Xing, Z.‐Y.; Chadwick, R.; Ma, Y.‐Z.; Ruohoniemi, J. M.; Lester, M.
Abstract: First experimental proof of a clear and strong dependence of the standard phase scintillation index (σφ ) derived using Global Positioning System measurements on the ionospheric plasma flow around the noon sector of polar ionosphere is presented. σφ shows a strong linear dependence on the plasma drift speed measured by the Super Dual Auroral Radar Network radars, whereas the amplitude scintillation index (S4 ) does not. This observed dependence can be explained as a consequence of Fresnel frequency dependence of the relative drift and the used constant cutoff frequency (0.1 Hz) to detrend the data for obtaining standard σφ . The lack of dependence of S4 on the drift speed possibly eliminates the plasma instability mechanism(s) involved as a cause of the dependence. These observations further confirm that the standard phase scintillation index is much more sensitive to plasma flow; therefore, utmost care must be taken when identifying phase scintillation (diffractive phase variations) from refractive (deterministic) phase variations, especially in the polar region where the ionospheric plasma drift is much larger than in equatorial and midlatitude regions. Key Points: A clear strong linear dependence of phase scintillation index on the plasma drift speed around noon sector of the polar ionosphere is presented Observed dependence can be very possibly explained by the dependence of the shifted Fresnel frequency from the relative drift Amplifies the importance of using dynamic cutoff frequency in detrending the phase of GPS signal in the polar region